Pomodoro Project for iPhone - An evaluation of the iPhone platform and a description of techniques for iPhone development. - Wahlman, Rasmus; Sandén, Michael (My University, 2010)
Mobile phones today are used for much more than just calling and text messaging people. As technology has become more advanced, developers have started to incorporate a wide variety of functionality into their phones, such as the ability to surf the web, listen to music and also run application on their phones. This report will deal with the evaluation of such a phone, namely the iPhone. This report will also deal with the development of an iPhone application, which is a digital version of the Pomodoro Technique, with large focus on usability and interaction design. The first part of the project constitutes for a pre-study part within the area of iPhone development as a whole with information about general iPhone development tools, frameworks, design and interface design patterns. Since there are many ways to implement a product which must have high user-friendliness and usability, we will therefore explain and discuss the process behind developing the Pomodoro Application and motivate our choices of design methods and general approach towards development. By working on this project, we have realised that developing applications for the iPhone is rather simple as long as the developer sticks to standard frameworks and interface patterns supported by the iPhone SDK itself. If you wish to create an interface of your own however, you will be forced to do it all by yourself and it will be much more time consuming in the end. Sammanfattning Mobiltelefoner används idag till mycket mer än bara telefonsamtal och textmeddelanden. I takt med att tekniken blir mer avancerad har företag börjat lägga in allt mer funktionalitet i sina telefoner, så som möjligheten att surfa på nätet, lyssna på musik och köra applikationer på sina telefoner. Denna rapport kommer behandla en evaluering av en sådan telefon, nämligen Apples iPhone. Rapporten kommer även behandla utvecklingen av en applikation till iPhone som är en digital version av Pomodoro-tekniken med stort fokus på användarvänlighet. Den första delen av projektet bestod utav en förstudie vars syfte var att få en överblick över iPhoneutveckling samt vilka ramverk och verktyg som finns att tillgå. Eftersom det finns många sätt att implementera och designa en applikation kommer rapporten även ta upp de metoder som används under utvecklingen av applikationen samt designmetoder för att ta fram ett användarvänligt gränssnitt. Det vi kommit fram till genom att göra det här projektet är att det är relativt enkelt att utveckla applikationer till iPhone så länge som man håller sig till standardramverk och vanliga interfacedesignmönster som används till iPhone. Om man däremot vill skapa ett användargränssnitt som är helt eget får man räkna med att få göra allt själv och att utvecklingen kommer ta mycket längre tid.
Keywords: Övrig informationsteknik; Other information technology